Studies on Homalolomeneae (Araeceae) of Borneo I. Four New Species and Preliminary Thoughts on Informal Species Groups in Sarawak - Peter C., Boyce; Wong Sin, Yeng (Singapore Botanic Garden, 2008)
Four new species of Homalomena (Araceae : Homalomeneae) are described from Sarawak. The current supraspecific taxonomy of the genus is reviewed and reasons for not recognizing at this time formal supraspecific units are justified although the need for species groupings is restated. In line with other large, taxonomically intractable groups, informal groups are proposed and circumscribed. All new species are illustrated.